Effect of acupuncture on neuroinflammation in animal models of Alzheimer’s disease: A preclinical systematic review and meta-analysis - Wu, Zhi-Guo; Huang, Ying-Jie; Wang, Tun-Yi; Deng, Chu-Yu; Xu, Zhi-Rui; Tang, Chun-Zhi (Frontiers in Aging Neuroscience, 2023)
Background: Despite neuroinflammation being an important component of the pathology of Alzheimer's disease(AD), effective therapies to alleviate neuroinflammation are still lacking. Many animal experiments in AD have found that acupuncture may ameliorate cognition by decreasing neuroinflammation and modulating cytokines, but its effects have not been systematically examined. We aimed to assess its efficacy on neuroinflammation in AD and to investigate the potential mechanisms. Method: The following databases were searched from inception until 24 August 2022: Web of Science, EMBASE, PubMed, the Cochrane Library, and China National Knowledge Infrastructure. Animal studies that reported the efficacy of acupuncture on neuroinflammation in AD were included. The SYRCLE Robt was utilized to evaluate methodological quality. Stata 17 was utilized to conduct a meta-analysis of cytokine levels and the results of the Morris water maze. Results: 23 studies were included, with a total of 417 rats/mice. The overall quality of all included reports was medium. The results indicated that acupuncture significantly reduced the expressions of pro-inflammatory cytokines which included IL-1β [SMD = − 3.50, 95% CI (− 4.31, − 2.69); I2 = 78.6%](P < 0.05), TNF-α [SMD = − 3.05, 95% CI (− 3.86, − 2.24); I2 = 69.6%] (P < 0.05), IL-6 [SMD = − 3.22, 95% CI (− 4.62, − 1.81); I2 = 77.6%] and enhanced the expressions of anti-inflammatory cytokines including IL-4 [SMD = 2.77, 95% CI (1.95, 3.59); I2 = 33.9%] (P < 0.05), IL-10 [SMD = 1.84, 95% CI (1.20, 2.49); I2 = 41.0%] (P < 0.05) in an animal model of AD. Regarding the Morris water maze, compared to the control group, the acupuncture group showed a shorter escape latency[SMD = − 2.23, 95% CI (− 2.89, − 1.57); I2 = 79.2%](P < 0.05), longer duration in platform quadrant[SMD = 2.34, 95% CI (1.44, 3.23); I2 = 81.7%](P < 0.05), and increased platform crossing number[SMD = 2.79, 95% CI (2.06, 3.53); I2 = 71.9%](P < 0.05). Conclusion: Acupuncture may reduce neuroinflammation in AD by modulating cytokine expression. This modulation significantly improved cognitive function in animal models of AD. Systematic review registration: PROSPERO registration no: CRD42022354878.